PENERAPAN PRINSIP STRICT LIBILITY DALAM PERTANGGUNGJAWABAN KORPORASI YANG DIANGGAP BERTANGGUNGJAWAB ATAS KEBAKARAN HUTAN DI PROVINSI RIAU - Pandiangan, Eko Ardiansyah; ', Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Strict liability system is a concept that is used to hold the perpetrators of criminal or corporation is a legal entity and the subject of people who commit criminal acts with a category of offenses. However, during the existence of corporate responsibility in environmental law recognized in practice was never found in cases of environmental pollution which punish corporations for example in the case of forest fires in Riau conducted by several companies in Riau.Issues discussed were the first, about how the application of the principle of strict liability in corporate responsibility which is considered responsible for forest fires in Riau province, both as to whether the impediments to criminal liability corporation on forest fires in Riau province, and the third how the efforts made by the Police regions (POLDA) Riau in tackling forest fires in Riau Province.The method used is empirical research, another term is sociological research is also called field research and descriptive research. In collecting the data, the type of data used in this study are primary data and secondary data, ie directly through written records and interviews of the Provincial Police Videos, Law No. 32 of 2009 on the Protection and Environmental Management, Law No. 41 1999 on Forestry, law journals and books related to the research. The data analysis was done qualitatively and conclusions drawn deductively.From the research conducted by the author of the application of the principle of strict liability has been done but there is still a lot of corporations that do not perform as it should be criminal liability, such as liability on the principle of strict liability.Keywords: Strict Liability - Liability Corporations - Forest Fires